Gambaran Tingkat Depresi Kecemasan dan Stress pada Penderita Diabetes Mellitus Tipe 2 di Puskesmas I Pucakwangi Kabupaten Pati - Izabela Ayu Pasya; Moch. Aspihan; Iskim Luthfa (Journal of Medical Practice and Research, 2026)
Type 2 diabetes mellitus is a chronic disease that not only affects physical condition but also affects the psychological health of sufferers, including depression, anxiety, and stress. This study aims to describe the levels of depression, anxiety, and stress in people with type 2 diabetes mellitus at the Pucakwangi Community Health Center in Pati Regency. This study used a descriptive observational design with a cross-sectional approach involving 117 respondents through total sampling. Data collection was conducted using the Depression Anxiety Stress Scale-21 (DASS-21) questionnaire. The results showed that most respondents experienced anxiety (82 patients, 70.0%), the majority did not experience stress (97 patients, 83.0%), and some respondents experienced varying levels of depression. The psychological conditions experienced by patients have the potential to affect blood glucose control and adherence to treatment and therapy. This picture shows that the management of Type 2 Diabetes Mellitus needs to consider psychological aspects as part of efforts to improve the quality of life of patients. A comprehensive approach between physical and psychological aspects is expected to support the success of therapy and prevent long-term complications